Qualitative Study of Content-Based Instruction in Maritime English Learning - Hafita, Yuniar Ayu; Sumarta, Ryan; Sulistiono, Agus; Widarbowo, Dodik (Meteor STIP Marunda, 2024)
This study investigates the impact of the Content-Based Instruction (CBI) approach on Maritime English learning among fourth-semester cadets at Sorong Merchant Marine Polytechnic. Using a qualitative method, observations were conducted over two months to assess cadet engagement, participation, and language use during CBI-based lessons. The findings indicate that integrating technical maritime content, such as navigation and emergency communication, significantly increased cadet motivation and engagement by making learning more relevant to their future careers. Cadets showed notable improvements in using specialized maritime terminology in both spoken and written tasks, demonstrating CBI's effectiveness in facilitating vocabulary acquisition and practical language skills. However, challenges emerged, including varying levels of English proficiency, which affected some cadets' ability to engage fully. While CBI supports technical language use, it does not entirely address foundational language gaps, such as grammar and pronunciation, suggesting a need for supplemental instruction. Overall, CBI is a promising approach for Maritime English education, enhancing language proficiency and professional skills, but further adaptations are required to accommodate all proficiency levels and ensure comprehensive learning outcomes.